2021
DOI: 10.1021/acs.energyfuels.1c01489
|View full text |Cite
|
Sign up to set email alerts
|

Oil Displacement Efficiency of a Silica/HPAM Nanohybrid

Abstract: In this study, the surface of silica nanoparticles (NPs) synthesized using the Stober method was modified with 3-aminopropyltriethoxysilane and hydrolyzed polyacrylamide (HPAM). The surface modification of the silica NPs was confirmed by Fourier transform infrared spectroscopy, field emission gun scanning electron microscopy, and thermogravimetric analysis. The characteristics of the nanopolymer sol were evaluated using rheology, viscosity retention ratio, interfacial tension, and contact angle measurements. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
(79 reference statements)
2
4
0
Order By: Relevance
“…An acceleration of the oil production was observed for the HPAM injection, although the final recovery factor of the nanopolymer sol was 1.3% higher at a lower concentration ( Figure 14 , green line). This oil recovery is comparable to that obtained in the laboratory tests previously reported by Corredor et al (2021), 73 where the displacement experiments showed that the nanopolymer sol increased the cumulative oil recovery by 2.2% OOIP compared to the HPAM solution. These results were attributed to the reduction of the capillary forces, the increment of the viscous forces, 73 and the contact of unswept oil areas due to the piston-like displacement of the chase water after the nanopolymer sol injection.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…An acceleration of the oil production was observed for the HPAM injection, although the final recovery factor of the nanopolymer sol was 1.3% higher at a lower concentration ( Figure 14 , green line). This oil recovery is comparable to that obtained in the laboratory tests previously reported by Corredor et al (2021), 73 where the displacement experiments showed that the nanopolymer sol increased the cumulative oil recovery by 2.2% OOIP compared to the HPAM solution. These results were attributed to the reduction of the capillary forces, the increment of the viscous forces, 73 and the contact of unswept oil areas due to the piston-like displacement of the chase water after the nanopolymer sol injection.…”
Section: Resultssupporting
confidence: 89%
“…The differential pressures obtained by numerical simulation and the laboratory displacement tests 73 were similar. The differential pressures estimated by numerical simulation during the CSNH-AC and HPAM injections were 34.8 and 9.1 psi, respectively.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Li et al conducted flow setup of a ternary composite oil repellent system in a sand-filled tube model and investigated the effects of wettability, permeability, and percolation distance on chromatographic separation of the ternary composite oil repellent system . The same experiment is set on artificial homogeneous core by Corredor, and the effects of injection volume, viscosity, and injection method on oil-repellent effect and chromatographic separation were studied. Liu et al analyzed the effects of injection rate and core permeability on chromatographic separation at the entrance end of cores on oil-free homogeneous cores . In the alkali-free ternary composite system, the component salt itself has a passivating effect with the metal surface.…”
Section: Introductionmentioning
confidence: 99%
“… 12 The same experiment is set on artificial homogeneous core by Corredor, and the effects of injection volume, viscosity, and injection method on oil-repellent effect and chromatographic separation were studied. 13 15 Liu et al analyzed the effects of injection rate and core permeability on chromatographic separation at the entrance end of cores on oil-free homogeneous cores. 16 In the alkali-free ternary composite system, the component salt itself has a passivating effect with the metal surface.…”
Section: Introductionmentioning
confidence: 99%